An overview of corporate governance models in financial institutions - Alam, Md Kausar; Ab Rahman, Suhaimi; Mustafa, Hasri; Mohammed Shah, Sabarina; Rahman, Md. Mizanur (Conscientia Beam LLC, 2019)
The paper illustrates the models of corporate governance in the aspects of its definition, nature of management and objectives along with its roles, regulation and power of various stakeholders in ensuring the accountability and the protection of the rights of various stakeholders from conventional and Islamic perspectives. These models are different in their characteristics, nature, culture, costume, epistemology, and country’s rules and regulation. However, the conventional models highlight the roles of shareholders, stakeholders, depositors, institutions, investors, and communities from the perspective of the nation’s demand and cultures. In contrast, the Islamic model of corporate governance consists of some roles and responsibilities such as the responsibilities to suppliers, customers, investment account holders, shareholders, management, the board of directors, competitors, Shariah supervisory boards, societies, and the employees from its spiritual and social commitments. Through the critical analysis of these models of corporate governance is deemed to help the empirical research on corporate governance model and develop a certain model of Islamic corporate governance. However, the paper may help to give a simple understanding of the corporate governance models in both the conventional and Islamic perspectives of financial institutions.